ChemInform Abstract: A Novel Single‐Phase White Light Emitting Phosphor Ca9La(PO4)5 (SiO4)F2:Dy3+: Synthesis, Crystal Structure and Luminescence Properties. Issue 22 (12th May 2016) - Liu, Haikun; Liao, Libing; Molokeev, Maxim S.; Guo, Qingfeng; Zhang, Yuanyuan; Mei, Lefu
Abstract: Ca9 La(PO4 )5 (SiO4 )F2 :Dy 3+ is prepared by solid state reaction of stoichiometric quantities of CaCO3, (NH4 )2 HPO4, SiO2, Dy2 O3, and excess NH4 HF2 as a flux ( 5% H2 /N2 reducing atmosphere, alumina crucible, 1450 °C, 5 h).